Modular Synthesis of Shape-Persistent Organic Cage Compounds: Molecular Precursors for a New Class of Permanent Porous Materials - Mastalerz, Michael (Synlett, 2013)
Discrete organic cage molecules have been introduced as molecular building units for highly porous materials. Here, an overview of the author’s contribution in this new field is given.
Keywords: imines; cage compounds; supramolecular chemistry; Schiff bases; self-assembly; porosity